A new species of the genus Plesiocoelus van Achterberg (Hymenoptera: Braconidae: Agathidinae) from Vietnam - Long, Khuat Dang; Achterberg, Cornelis van (Academia Journal of Biology, 2016)
Plesiocoelus van Achterberg is a rare genus of the subfamily Agathidinae (Braconidae). The genus was established by van Achterberg in 1990 with one Neotropical species included, Plesiocoelus bassiformis van Achterberg, 1990. Based on specimens deposited at the Institute of Ecology & Biological Resources (IEBR) and Vietnam National Museum of Nature (VNMN), the genus Plesiocoelus van Achterberg is newly recorded from Vietnam with a new species, Plesiocoelus vietnamicus Long & van Achterberg, sp. n. described and illustrated in this paper. Differences between the new species and P. bassiformis van Achterberg, are given.